Chemical Composition, Diuretic, and Antityrosinase Activity of Traditionally Used Romanian Cerasorum stipites - Babotă, Mihai; Voştinaru, Oliviu; Păltinean, Ramona; Mihali, Cosmin; Dias, Maria Inês; Barros, Lillian; Ferreira, Isabel C. F. R.; Mocan, Andrei; Crişan, Ovidiu; Nicula, Cristina; Crişan, Gianina (Frontiers in Pharmacology, 2021)
Cherry stems (CS) represents a by-product intensively used in Eastern European countries as a traditional remedy for urinary tract disorders. Ethnopharmacological evidences sustain the use of CS as aqueous preparations (infusion, decoction), but few data were previously reported about phytochemical profile and pharmacological potential of CS hydroalcoholic extracts. In this regard, we aimed to evaluate the phenolic profile, in vitro antioxidant and tyrosinase-inhibitory potential and in vivo diuretic activity of 70% hydroethanolic cherry stems extract (CSE) and cherry stems decoction (CSD). LC-DAD-ESI/MSn analysis revealed the presence of flavonoid-type compounds as main constituens for both preparations, especially flavanones (naringenin glycosides). Antioxidant and diuretic activity were superior for CSE, probably due to the presence of phenolic-derived compounds in higher amounts than CSD. On the other hand, tyrosinase inhibitory potential exerted by CSD was stronger, highlighting that other types of hydrophilic secondary metabolites are responsible for this bioactivity. Overall, our findings indicates that CS preparations could be used as promising mild diuretic agents, and encourage further investigations regarding the corelation between their chemical composition and bioactive potential.